Early transition metal-catalyzed C–H alkylation: hydroaminoalkylation for Csp3–Csp3 bond formation in the synthesis of selectively substituted amines. Issue 89 (18th October 2018) - Edwards, P. M.; Schafer, L. L.
Abstract : Protecting group, directing group, and external oxidant free synthesis of structurally diverse amines. Abstract : Hydroaminoalkylation is a 100% atom economic method for forming Csp 3 –Csp 3 bonds through C–H activation α to an amine and subsequent reaction with an alkene. When catalyzed by early transition metals, this reaction allows for alternative disconnections for the synthesis of structurally complex amines. This method avoids the installation of protecting groups or directing groups and does not require added oxidants, or photoredox catalysts. In this feature article, we discuss the various selectively substituted amines that can be accessed by hydroaminoalkylation, with a special focus on the development of early transition metal catalysts for their rapid, step and atom efficient assembly.